Statin Adherence and Mortality in Patients Aged 80 Years and Older After Acute Myocardial Infarction. Issue 10 (17th June 2019) - Phan, Derek Q.; Duan, Lewei; Lam, Bryan; Hekimian, Avetis; Wee, David; Zadegan, Ray; Lee, Ming‐Sum
Abstract : BACKGROUND/OBJECTIVES: The goal of this study was to describe the pattern of statin adherence in older patients, aged 80 years or older; identify factors associated with high adherence; and determine the association between statin adherence and all‐cause mortality. DESIGN: Retrospective population‐based cohort study. SETTING: An integrated healthcare system in Southern California. PARTICIPANTS: Patients hospitalized with a principal diagnosis of acute myocardial infarction (MI) between January 1, 2006, and December 31, 2016. MEASUREMENTS: Statin adherence, as measured using pharmacy dispensing records over the 365 days following hospital discharge, based on proportion of days covered (PDC). Adherence levels were categorized as high (PDC 80% or higher), partial (PDC 40% or higher and lower than 80%), and low (PDC lower than 40%). RESULTS: Between 2006 and 2016, 5629 patients, 80 years or older, hospitalized for acute MI met the inclusion criteria. Among this group, 68.8% were highly adherent to statin therapy, 20.4% were partially adherent, and 10.8% were not adherent. Male sex (odds ratio [OR] = 1.42; 95% confidence interval [CI] = 1.25‐1.62) and white race (OR = 1.35; 95% CI = 1.18‐1.55) were associated with high statin adherence. Follow‐up was 4.3 ± 2.6 years. Both low and partial adherence were associated with increase mortality (low adherence: adjusted hazard radio [HR] = 1.12; 95% CI = 1.01‐1.25; partial adherence: adjusted HR = 1.22; 95% CI = 1.12‐1.32). CONCLUSIONS: In older patients, aged 80 years or older, high adherence to statins after MI was associated with improved survival. This association may not have been due only to adherence to statins but to other related factors as well. Findings from this study may inform discussions on the potential benefits of statin adherence. J Am Geriatr Soc 67:2045–2049, 2019